STUDENT SATISFACTION ANALYSIS OF ADMINISTRATIVE SERVICE PERFORMANCE AT PROFESSIONAL STMIK - Kurnia Yahya; Suardi Hi Baharuddin; Satriawaty Mallu; Nasaruddin (Nusantara Hasana Journal, 2023)
This study aims to determine student satisfaction with STMIK Professional Academic Administration Services based on Tangibles, Responsiveness, Reliability, Empathy, and Assurance aspects. descriptive with a quantitative approach. The population of this study was 454 students of the 2018-2021 STMIK Professional class. The sampling technique was carried out by proportional stratified random sampling. The sample size is 100 people. The data collection technique used an attitude scale. The data analysis technique used a trend test and the percentage of the frequency distribution of each aspect of satisfaction